2016
DOI: 10.1038/mp.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Depression and risk of type 2 diabetes: the potential role of metabolic factors

Abstract: The aim of the present study was to evaluate the interaction between depressive symptoms and metabolic dysregulations as risk factors for type 2 diabetes. The sample comprised of 2525 adults who participated in a baseline and a follow-up assessment over a 4.5-year period in the Emotional Health and Wellbeing Study (EMHS) in Quebec, Canada. A two-way stratified sampling design was used, on the basis of the presence of depressive symptoms and metabolic dysregulation (obesity, elevated blood sugar, high blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…18,19,25 Central obesity was defined as having waist circumference of greater than or equal to 94 cm for European men and greater than or equal to 80 cm for European women. These risk factors were chosen as they have been used in previous work to identify cardiometabolic abnormalities.…”
Section: Cardiometabolic Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19,25 Central obesity was defined as having waist circumference of greater than or equal to 94 cm for European men and greater than or equal to 80 cm for European women. These risk factors were chosen as they have been used in previous work to identify cardiometabolic abnormalities.…”
Section: Cardiometabolic Abnormalitiesmentioning
confidence: 99%
“…These risk factors were chosen as they have been used in previous work to identify cardiometabolic abnormalities. 18,19,25 Central obesity was defined as having waist circumference of greater than or equal to 94 cm for European men and greater than or equal to 80 cm for European women. Raised triglycerides were greater than or equal to 1.7 mmol/L and reduced HDL cholesterol is less than 1.0 mmol/L in males and and less than 1.3 mmol/L in females.…”
Section: Cardiometabolic Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One analysis of prospective longitudinal studies found that depression is associated with a higher incidence of type 2 diabetes, accounting for a 60% increased risk. However, in another longitudinal study, higher risk of incident diabetes was only observed in those individuals with both depressive symptoms and metabolic dysregulation, but not in those with depressive symptoms and without metabolic dysregulation. A meta‐analysis of longitudinal studies reported a 25% increased risk of incident depression in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has suggested that the risk of type 2 diabetes is greatest among individuals with both elevated depressive symptoms and metabolic dysregulation relative to individuals with only depressive symptoms, a group whose risk was similar to individuals without either depressive symptoms or metabolic dysregulation [56]. Studies have reported that the presence of depression increases threefold the odds that patients will be noncompliant with medical treatment recommendations [57].…”
Section: Resultsmentioning
confidence: 99%